2018
DOI: 10.14366/usg.18013
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal ultrasound: athletic injuries of the lower extremity

Abstract: Athletic injuries of the lower extremities are commonly encountered in clinical practice. While some pathology can be diagnosed on physical exam, others are a clinical dilemma with nonspecific symptomatology. In these situations, ultrasound imaging can be utilized as an exceptional diagnostic tool, offering unique advantages over other imaging modalities. This article will review the imaging characteristics of commonly encountered athletic injuries of the lower extremity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Ultrasound allows for assessing tendons in a more dynamic real time setting [15]. The physician can interact with patients and receive feedback regarding the symptomatic area, assessing the tendon from different angles while under stress [15] [16] [17]. It also has the ability to evaluate the changes in tendon length during contraction [18].…”
Section: Advantages Of Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound allows for assessing tendons in a more dynamic real time setting [15]. The physician can interact with patients and receive feedback regarding the symptomatic area, assessing the tendon from different angles while under stress [15] [16] [17]. It also has the ability to evaluate the changes in tendon length during contraction [18].…”
Section: Advantages Of Ultrasoundmentioning
confidence: 99%
“…In contrast to other modalities, ultrasound necessitates a highly skilled operator [11] [17]. For example, fresh tears especially those of distal ruptures are easy to detect by experienced physicians [11].…”
Section: Disadvantage Of Ultrasoundmentioning
confidence: 99%
“…Plantar fasciopathy (PF) is a musculoskeletal condition that affects the plantar fascia, which is a thick band made by connective tissue that runs from the calcaneal tuberosity forward to the heads of the metatarsal bones, helping to maintain the stability and the arch of the foot (Hormozi et al, 2011;Petraglia et al, 2017). The plantar fascia is divided into three cords, with the central one being the thickest and the most often injured (Meyer et al, 2018). PF was formerly known as "plantar fasciitis", but this term is obsolete, since inflammation is absent in this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Shear wave elastography (SWE) allows quantitative assessment of the stiffness of the plantar fascia and can highlights the classic alterations of PF Schillizzi et al, 2020;Vola et al, 2018). Contrary to popular belief, recent studies have demonstrated no correlation between fascial thickness and degree of symptoms (Meyer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…8 According to national health survey around 3 persons have OA per 10 people with disabilities. 9 In order to improve treatment outcome, X-ray, CT-scan, Arthroscopy, Ultrasound (US) and Magnetic Resonance Imaging (MRI) imaging modalities have been used to monitor and diagnosis knee problems. However, X-ray and CT-scan use ionizing radiation which causes cancer and might result different stochastic and deterministic effects.…”
Section: Introductionmentioning
confidence: 99%